2023
DOI: 10.3390/ijms242316935
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Transposable Elements in Strawberry Genomes of Different Ploidy Levels

Keliang Lyu,
Jiajing Xiao,
Shiheng Lyu
et al.

Abstract: Transposable elements (TEs) make up a large portion of plant genomes and play a vital role in genome structure, function, and evolution. Cultivated strawberry (Fragaria x ananassa) is one of the most important fruit crops, and its octoploid genome was formed through several rounds of genome duplications from diploid ancestors. Here, we built a pan-genome TE library for the Fragaria genus using ten published strawberry genomes at different ploidy levels, including seven diploids, one tetraploid, and two octoplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Analysis of strawberry pangenomes also resulted in interesting findings about strawberry evolution and domestication. Based on transposable element analysis of a pangenome constructed from 10 high-quality strawberry genomes, Lyu et al (2023) suggested that Fragaria viridis may not be one of the diploid Fragaria ×ananassa ancestors as previously thought. Additionally, Qiao et al (2021) discovered a new diploid strawberry species during assembly of their own pangenome.…”
Section: Multi-omics Approaches For Trait Discovery For Improving Str...mentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of strawberry pangenomes also resulted in interesting findings about strawberry evolution and domestication. Based on transposable element analysis of a pangenome constructed from 10 high-quality strawberry genomes, Lyu et al (2023) suggested that Fragaria viridis may not be one of the diploid Fragaria ×ananassa ancestors as previously thought. Additionally, Qiao et al (2021) discovered a new diploid strawberry species during assembly of their own pangenome.…”
Section: Multi-omics Approaches For Trait Discovery For Improving Str...mentioning
confidence: 99%
“…Evolutionary analysis of Fragaria ×ananassa suggested genomic contributions of four diploid progenitor species: Fragaria vesca, Fragaria iinumae, Fragaria viridis, and Fragaria nipponica (Edger et al, 2019;2020). However, analysis from other groups has suggested that both F. viridis and F. nipponica are not among the diploid progenitors (Liston et al, 2020;Jin et al, 2023;Lyu et al, 2023;Session and Rokhsar, 2023). As identification of the progenitor species may enable greater prediction of polyploid responses to environmental stress and climate change (Liston et al, 2020), further analysis of the evolutionary history of strawberry will be necessary to confirm the identities of the diploid progenitor species.…”
Section: Introductionmentioning
confidence: 99%